PENGARUH DIVERSITAS GENDER DEWAN DIREKSI, KOMPENSASI EKSEKUTIF, DAN KEPEMILIKAN MANAJERIAL TERHADAP PENGHINDARAN PAJAK - Riswandi, Bunga Edelwisha Arisandi; Basri, Yesi Mutia; Azhari S (Fakultas Ekonomi dan Bisnis Universitas Bung Hatta, 2024)
This research aims to analyze and test the negative influence of Board of Directors Gender Diversion, the positive influence of Executive Compensation and the negative influence of Managerial Ownership on tax avoidance. Consumer Non-Cyclicals manufacturing companies that have been listed on the IDX in 2018-2022 are the population used in this research. In this research, sampling was carried out using a purposive sampling method and 39 data were obtained. In this research, the data source used is secondary data obtained through annual reports of companies in the Consumer Non-Cylicals sector that have been listed on the IDX from 2018 to 2022. The data analysis method used in this research is classical assumption testing and hypothesis testing using the linear regression method. Multiple. Based on the results of data analysis using the t test, it appears that gender diversity of the board of directors and share ownership are able to influence tax avoidance partially and negatively, while executive compensation is unable to influence tax avoidance.